Delegitimization Of Religious Motives in Polygamy in Banjar Society - Dahli, Zainal Muttaqin; Umar, Masyithah; Mujiburohman, Mujiburohman; Rusdiyah, Rusdiyah; Sa'adah, Sa'adah; Khalid Seff, Nadiyah (Syariah: Jurnal Hukum dan Pemikiran, 2024)
In fact, the practice of polygamy in the Banjar community is often carried out without being recorded and gives rise to legal problems, not only in the form of not fulfilling the right to justice but also gives rise to physical, verbal, and psychological violence. It is often that religion becomes a 'shield' in the form of unconscious motives to cover up the truly practical motives. The purpose of this writing is to describe why the practice of polygamy in Banjar society, with its duality of motives, actually creates problems and why religion is always a 'shield'. This research was conducted empirically with data obtained from the interview process with informants and then analyzed using a socio-legal approach. Based on the results of the study, it was found that the practice of polygamy for religious reasons as an unconscious motive has the potential to give rise to unfair polygamous behavior, acts of violence, and a disregard for the protection of rights and the law. The textual and partial interpretation of polygamy texts supported by a patriarchal socio-cultural system is the basis for legitimizing this behavior, even though this behavior is not by the essential goals of marriage including polygamy and the applicable regulations. Making religion an unconscious motive is something that is considered effective in legitimizing polygamy because, by the religious character of Banjarese society with Islam being an ethnic identity, the practice of polygamy is understood as a natural and legitimate thing.  This condition is strongly supported by the traditionalist reasoning that many Banjar people adhere to so that often the understanding of a tuan guru includes polygamy as an accepted truth. This is because of the position of the tuan guru who is considered as an authoritative figure in every aspect of Banjarese people's life.